Fostering sustainability in environmental performance via ESG metrics: the significance of management approach and leadership aspiration - Lee, Yen Min (2023)
There is an increasing trend that both multinational companies and local companies are involved in Environment, Social and Governance (ESG) compliance and reporting requirements. This is because companies have now realised the importance of ESG and ESG has become a topic, additionally, there is an increase in ESG compliance screening, and also macro environmental issues such as global warming and pollution issues are developing to a more severe stage. In order to guide companies to manage and report their ESG performance, plenty of ESG reporting frameworks have been developed such as Global Reporting Initiative (GRI) framework, Task Force on Climate-related Financial Disclosures (TFCD). This research is interested in the current involvement of Malaysia listed companies in environmental practice. Besides assessing the environmental performance level, the relationship between firm’s financial performance and its environmental performance is investigated as well. This research examined the impact of stakeholder management and target setting approach on firm’s environmental performance. This thesis also attempted to reveal the impact of different industry environmental sensitivity level and impact of leadership aspiration on a firm’s environmental performance level.